2011
DOI: 10.1007/s11249-011-9804-8
|View full text |Cite
|
Sign up to set email alerts
|

From Continuous to Molecular Scale in Modelling Elastohydrodynamic Lubrication: Nanoscale Surface Slip Effects on Film Thickness and Friction

Abstract: The aim of this article is to propose an original approach in modelling elastohydrodynamic lubrication (EHL), combining a classical model derived from continuum mechanics and a nanoscale investigation carried out by Molecular Dynamics simulations. In particular, nanoscale slip is numerically quantified and a semi-analytical model for surface slip variation with pressure, film thickness and sliding velocity is presented. A composite model involving both continuum mechanics and nanoscale effects allows for a bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…These simulations have shown that the slip length generally increases with increasing sliding velocity and pressure [168][169][170][171]. At very high sliding velocity, the slip length asymptotes towards a constant value [57].…”
Section: Boundary Slipmentioning
confidence: 87%
See 2 more Smart Citations
“…These simulations have shown that the slip length generally increases with increasing sliding velocity and pressure [168][169][170][171]. At very high sliding velocity, the slip length asymptotes towards a constant value [57].…”
Section: Boundary Slipmentioning
confidence: 87%
“…This can lead to large reductions in friction compared to the Couette case [146]. Slip has been commonly observed in NEMD simulations of thin fluid films confined between atomically-smooth surfaces [57,[168][169][170][171]. Many of these studies have quantified the slip length, which is defined as an extrapolated distance into the wall where the tangential velocity component vanishes (see Fig.…”
Section: Boundary Slipmentioning
confidence: 99%
See 1 more Smart Citation
“…As the EHL films in contacts lubricated by very low viscosity oils can be ultra thin, i.e., in the range of few nanometres, the use of a continuum model of lubricant flow becomes questionable [78]. In these ultra-thin films molecular characteristics control the onset of slip inside the EHL contact.…”
Section: Non-newtonian Lubricant Rheology and Ehlmentioning
confidence: 99%
“…The regulating factor is that the amount of slip is inversely proportional to the film thickness, i.e., thicker film results in smaller slip. In such cases the molecular dynamic simulations provide better understanding of the phenomena occurring than the continuum models [78].…”
Section: Non-newtonian Lubricant Rheology and Ehlmentioning
confidence: 99%